1991
DOI: 10.1007/bf01613138
|View full text |Cite
|
Sign up to set email alerts
|

Expression of metalloproteinase genes in human prostate cancer

Abstract: Twenty-five surgical specimens of malignant human prostate, 3 lymph nodes with metastatic prostate carcinoma, 11 normal human prostates, as well as 3 human prostate cell lines (DU-145, PC3 and LNCaP) were examined for the expression of the human matrix metalloproteinase-7 gene (MMP-7) from the human collagenase family (originally called PUMP-1 for putative metalloproteinase-1) [Quantin et al. (1989) Biochemistry 28:5327-5334; Muller et al. (1988) Biochem J 253:187-192; Matrisian and Bowden (1990) Semin Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
100
2
5

Year Published

1998
1998
2003
2003

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(109 citation statements)
references
References 16 publications
2
100
2
5
Order By: Relevance
“…Cancer outcome studies have also shown that increased expression of MMPs is associated with shortened patient survival (10,12,46). Aberrant expression of MMPs in prostate cancer was first described using in situ hybridization in 1991 (31). MMP7 expression has been linked to prostate cancer pathologic stage and incidence of metastasis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer outcome studies have also shown that increased expression of MMPs is associated with shortened patient survival (10,12,46). Aberrant expression of MMPs in prostate cancer was first described using in situ hybridization in 1991 (31). MMP7 expression has been linked to prostate cancer pathologic stage and incidence of metastasis (33).…”
Section: Discussionmentioning
confidence: 99%
“…MMPs have an important physiological role in embryonic development (Brenner et al, 1989), bone remodelling (Delaisse and Vaes, 1992) and wound healing (Wolf et al, 1992), and a major role in pathological processes including rheumatoid arthritis (Harris, 1990) and cancer invasion and metastasis (Liotta and Stetler-Stevenson, 1991). MMP overexpression has been reported in carcinomas of the ovary (Campo et al, 1992), prostate (Pajouh et al, 1991) and lung (Brown et al, 1993) and MMP activity correlated with malignant potential in gastric (Nomura et al, 1995) and colorectal (Mori et al, 1995;Porte et al, 1995) cancer.…”
mentioning
confidence: 99%
“…In contrast to the expression of these gelatinolytic enzymes (with type IV collagenolytic activity), there is little evidence for elaboration of enzymes which can degrade interstitial connective tissue. Pajouh et al (1991) reported that mRNA for MMP-1 (interstitial collagenase) was not detectable in either normal or malignant prostate specimens. MMP-1 immunoreactivity was detected in plasma of prostate cancer patients, but the amount detected was not significantly different from amount present in normal volunteers (Jung et al, 1997).…”
mentioning
confidence: 99%